Marital wellbeing indicators amongst Malay Muslim couple in Malaysia: A preliminary study - Mohd Noor, Norhayati; Mohd Mahdzir, Akbariah; Nor, Azmawaty Mohamad; Abdullah, Rohaya (UPM Press, 2019)
Introduction: There is a significant increase in the number of divorce cases among Malay Muslim couples over the past years which serves as a strong signal for the government to take initiatives to understand the current situation. A plethora of literature can be found on marriage satisfaction and the quality of the relationship within marriages. However, exploration on contributing factors to long lasting marriages amongst the Malay Muslim community are lacking. This paper aims to share the initial findings in an effort to explore of the strength of relationship in a lasting marriage amongst Malay Muslim couples in Malaysia. Methods: This paper adopted a quantitative approach utilizing the Eternal Love Instrument (c) 2016 which consisted of 171 items, distributed to 350 respondents based on simple random sampling technique. Results: The findings indicated that there are three main considerations in selecting a spouse which were (1) Religion (95.2%); (2) Character (responsible) (96.1%); well mannered (95.8%); and (3) Race (79.3%). Age, looks and type of jobs were the least considered factors amongst the respondents surveyed. The respondents perceived that the strongest element in their relationship was communication (69.6%), followed by tolerance (62.6%) and responsible towards family wellbeing (56.4%). Conclusion: The initial survey has indicated that a lasting marriage is a consequence of having a responsible partner with good religious background. Also, from all these five constructs, these respondents considered their spouses to be highly responsible. © 2019 UPM Press. All rights reserved.